Green Tradable Certificates versus Feed-in Tariffs in the Promotion of Renewable Energy Shares - Till Requate (Center for Economic Studies and ifo Institute (CESifo), 2014)
The paper analyzes the relationship between CO2 mitigation policy and promotion policies designed to deploy renewable energy sources for electricity production (RES-E). If an emission cap is the only policy target, an optimal mix consisting of high and low carbon use of fossil fuels, deployment of RES-E, and energy savings can best be achieved by either setting a uniform carbon tax or by implementing a cap-and-trade system covering all CO2 sources. An additional RES-E share target causes higher costs in achieving the cap. Conversely, a more ambitious emission target automatically increases the RES-E share. In a second step we investigate different policies for inducing an RES-E quota. Such a quota can be efficiently achieved either by a system of tradable green certificates or by a budget-balancing premium system. A budget-balancing FIT system, by contrast, is not efficient, since it generates excessive fiscal distortion. We also show that differentiated, technology-specific FITs are even more inefficient.
Keywords: L38; L51; L94; Q28; Q42; Q55; 330; feed-in tariffs; tradable green certificates; premium systems; emission cap; cap and trade